Factors influencing electronic commerce adoption in developing countries: The case of Tanzania - W. H. Makame; J. Kang; S. Park (South African Journal of Business Management, 2014)
Electronic commerce is rapidly replacing the old ways of doing business. Although many studies have been conducted on the adoption of various forms of e-commerce, there are few on this topic in African countries; in particular, there is no research on Tanzania. Therefore, this paper analyzes the factors determining e-commerce and their impact on its adoption in Tanzania. This paper extends the technology acceptance model (TAM) to an empirical study analyzing the factors influencing e-commerce adoption in Tanzania. A survey involving 111 respondents including Tanzanian government officers was conducted, and structural equation modeling was used to assess the model for the influence of three new factors: national policy initiatives, technology infrastructure, and trust in e-commerce adoption. The results show thattechnology infrastructure is an important factor in e-commerce adoption, and national policy initiatives are important in building online trust and improving technology infrastructure in Tanzania. Therefore, government policy makers need to encourage the presence of good technology infrastructure and build trust in e-commerce through national policy initiatives such as e-commerce promotion. Limitations of this paper are that the respondents are limited to people who have access to the Internet and some might not have enough knowledge about e-commerce. Further, the survey is conducted only in Tanzania; therefore, the results may differ in other African countries.
Keywords: 650